IMPLEMENTASI KEBIJAKAN FULL DAY SCHOOL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMAN 8 BATANGHARI - Nurul Padila; Denny Denmar; Agus Lestari (STKIP Pesisir Selatan, 2026)
This research was motivated by the implementation of the Full Day School policy at SMAN 8 Batanghari, which still faces various challenges in improving students’ learning motivation. The implementation of the Full Day School system requires effective learning management in order to create a conducive learning environment and increase student involvement in the learning process. This study aims to determine the implementation of the Full Day School policy in improving students’ learning motivation at SMAN 8 Batanghari. This research used a qualitative approach with a case study design. Data collection techniques were conducted through interviews, observations, and documentation, while data validity used source triangulation and technique triangulation. The results showed that the implementation of the Full Day School policy had been carried out through integrated intracurricular, cocurricular, and extracurricular activities. This system was able to improve students’ discipline, activeness, and learning motivation, as well as provide opportunities for students to develop their interests and talents. However, there were still several obstacles in its implementation, such as learning boredom due to long study hours, limited facilities and infrastructure, and students’ physical and mental fatigue. Supporting factors in implementing this policy included support from the school, teachers, parents, and varied and well-directed learning activities.